1992
DOI: 10.1111/j.1365-2125.1992.tb04054.x
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective disposition of flurbiprofen in normal volunteers.

Abstract: 4'-hydroxyflurbiprofen. There was significant enantioselectivity (R > S) in the formation clearances of these metabolites which remained when unbound metabolite formation clearances were considered. 5 In conclusion, the disposition of the enantiomers of flurbiprofen exhibits enantioselectivity at the level of protein binding and metabolite formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
17
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 29 publications
5
17
2
Order By: Relevance
“…In addition, using rat liver microsomes and human liver microsomes, it was shown that the amount of metabolized (R)-flurbiprofen was greater than the amount of (S)-flurbiprofen, [7,8]. And, faster elimination of the (R)-enantiomer was reported in normal volunteers with the similar distribution volumes of the drug [9]. The observed pharmacokinetic differences between both enantiomers in previous studies reflect the findings in this study.…”
Section: Resultssupporting
confidence: 78%
“…In addition, using rat liver microsomes and human liver microsomes, it was shown that the amount of metabolized (R)-flurbiprofen was greater than the amount of (S)-flurbiprofen, [7,8]. And, faster elimination of the (R)-enantiomer was reported in normal volunteers with the similar distribution volumes of the drug [9]. The observed pharmacokinetic differences between both enantiomers in previous studies reflect the findings in this study.…”
Section: Resultssupporting
confidence: 78%
“…Unlike in rats [5,[10][11], kinetic interactions between the isomers of flurbiprofen do not appear to occur to a significant extent in humans as the enantioselective differences following racemate administration [2][3][4] were of the same magnitude as those found in the present study after administration of single enantiomers. In conclusion, flurbiprofen does not undergo gesic may be that it may lack the gastrointestinal toxicity associated with the (S)-enantiomer, as demonstrated in rats [1].…”
Section: Discussionsupporting
confidence: 62%
“…Previously, we reported the disposition of R-and Sflurbiprofen in a group of normal volunteers (Knadler et al, 1992). When compared with normal subjects the uraemic patients exhibit significantly greater (P < 0.05) values of oral clearance (R:38.3 ± 12.8 vs 20.4 ± 4.7; S: 30.8 ± 11.5 vs 16.1 ± 3.6 ml min-') and volume of distribution (R: 17.6 ± 3.9 vs 9.1 ± 1.8; S: 14.6 ± 2.5 vs 8.5 ± 1.3 1).…”
Section: Discussionmentioning
confidence: 99%